Empowerment of health cadres in detecting psychosocial problems for chronic tuberculosis patients in Bulu, Sukoharjo - Arum Pratiwi; Erna Herawati; Abi Muhlisin; Nuralis Setyadi; Dian Hudiyawati; Kartinah Kartinah (Community Empowerment, 2023)
Bulu Community Health Center currently treats 24 Tuberculosis (TB) sufferers, 143 people in the risk group and has 30 health cadres. TB sufferers need comprehensive treatment including physiological and psychological problems. Psychological treatment for TB sufferers has not been carried out due to limited health personnel and lack of knowledge about how to detect psychosocial problems early and treat them. The aim of this community service is to obtain data on TB patients who experience psychosocial problems and increase health cadres' knowledge about detecting psychosocial problems and how to treat them. This program was carried out in the form of training and mentoring for 15 health cadres. Based on the evaluation results, the level of cadre knowledge about the concept of TB increased from 66.7 to 82.1 and the concept of depression increased from 56.4 to 72.2. Furthermore, skills in early detection increased from 52.3 to 76.5.